KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA TABARU SUATU ANALISIS KONTRASTIF - KALATJO, ARDIYANTO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This study is an attempt to analyze, describe and contrast English and Tabaru languages which focuses on the interrogative sentences in relation to their forms and functions in both languages. The writer analyzed interrogative sentences based on the concept of Frank (1972), and contrasted them by using Lado’s theory (1957). The result of this study is that these two languages have differences as well as similarities. The similarities are that both languages have interrogative-word question and yes-no questions, and the differences is that English has tag-questions while Tabaru does not. The difference is also interrogative-word questions in Tabaru has more specific word questions while English does not. English has only the Wh-Question who to ask about people but Tabaru has nago’ona (to ask people generally and third person plural), nagu’una (for man) and nagu’muna (for woman). In addition English has the Wh-Question when to ask about period of time while Tabaru has kauruosi (past) and muruoka (future). In English, word question is in the beginning of the sentence while in Tabaru in the beginning, middle and at the end of the sentence. Keywords : Interrogative Sentence, English, Tabaru Language, Contrastive Analysis.